Johannesburg: Instransigent nubs of meaning: Examining the nomosphere through Koleka Putuma’s "Collective Amnesia" - M. Llobera, Laia (Tropelías: Review of Literary Theory and Comparative Literature, 2024)
This research paper delves into the intersection of critical thinking, comparative literature, and urban theory by examining Emily Apter’s theory of the untranslatable in the context of South African poet Koleka Putuma’s poetry book, Collective Amnesia. Apter’s concept of the untranslatable serves as a theoretical framework to analyze Putuma’s utilization of untranslatable elements within her poetry as a means of resistance against colonial discourse. Specifically, the paper argues that Putuma strategically employs untranslatables to challenge and disrupt the colonial reader’s expectations and interpretations, thereby asserting agency and autonomy within the literary space. Furthermore, this paper explores how the untranslatables utilized by Putuma offer insights into the intricacies of Johannesburg as a contested urban space. Drawing from contemporary urban theory, particularly David Delaney’s conception of the nomosphere, the paper analyzes how Putuma’s incorporation of untranslatable elements within her poetry provides a nuanced understanding of Johannesburg’s complex social, cultural, and historical dynamics. Through close textual analysis, the paper uncovers the ways in which untranslatables function as symbolic markers that reveal the nomospheric layers of the city, shedding light on its spatial politics, power dynamics, and socio-cultural tensions.